Pemanfaatan Digital Marketing dalam Memasarkan Produk Pakaian Melalui Media Sosial Instagram: Studi Kasus pada Brand Syndicatesroom - Dai Muhammad Damara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The large number of internet users in Indonesia is the main reason business people use digital marketing to attract consumers. Syndicatesroom as a local Tangerang brand with a streetwear theme, Syndicatesroom provides a platform for young people to collaborate, share ideas, channel creativity in a forum called a syndicate. This research is entitled the use of digital marketing in marketing clothing products via Instagram social media (case study of the Syndicatesroom brand). This research aims to determine the process of using digital marketing carried out by Syndicatesroom in marketing clothing products on Instagram social media. This research uses a constructivist paradigm using qualitative methods using primary and secondary data sources as well as interview observations. The data sources used are journals, websites and Syndicatesroom social media. The results of this research show that Syndicatesroom has succeeded in utilizing digital marketing in marketing clothing products via Instagram social media. Syndicate, as a pioneering and independent company in selling products as a marketing tool, requires an effective strategy to increase sales.